PRODUCT INNOVATION FOR CONSUMERS AT THE BOTTOM OF THE PYRAMID: EVIDENCES IN THE BRAZILIAN CONTEXT (Gestão & Regionalidade, 2019)
This paper aims to analyze how product innovation has been developed for consumers at the bottom of the pyramid in the Brazilian context. To this end, this work was developed as a multiple case study assessing three firms operating in different sectors. The study found that the analyzed firms use sequential product development; that innovations for the bottom of the pyramid in Brazil are new-market disruptive, and that the firms use multiple innovation strategies to implement innovations in the bottom-of-the-pyramid market in Brazil. This study's findings contribute to broadening the understanding of types, dimensions and characteristics both of innovations and innovation strategies employed to cater to the low-income consumer market in Brazil.
Keywords: Innovation; Low income; Disruption; Strategy; Product development